Risk of breast cancer after miscarriage or induced abortion: a Scottish record linkage case-control study. - Brewster, D; Stockton, D; Dobbie, R; Bull, D; Beral, V (2005)
STUDY OBJECTIVE: To assess the risk of breast cancer in patients with a previous history of miscarriage or induced abortion. DESIGN: Case-control study relating "exposure" to outcome by linkage of national hospital discharge and maternity records, the national cancer registry, and death records. SETTING: Scotland. PARTICIPANTS: Miscarriage analysis-2828 women with breast cancer and 9781 matched controls; induced abortion analysis-2833 women with breast cancer and 9888 matched controls. MAIN RESULTS: After stratification for age at diagnosis, parity, and age at first birth, the odds ratio (95% confidence intervals) of breast cancer was 1.02 (0.88 to 1.18) in women with a previous miscarriage, and 0.80 (0.72 to 0.89) in women with a previous induced abortion. Further adjustments for age at bilateral oophorectomy, socioeconomic status (based on small area of residence), and health board area of residence had only minor effects on these odds ratios. CONCLUSION: These data do not support the hypothesis that miscarriage or induced abortion represent substantive risk factors for the future development of breast cancer.